Reanalysis on Phylogeographic Pattern of Sharpbelly Hemiculter leucisculus (Cyprinidae: Cultrinae) in China: A Review and the Implications for Conservation - Gu, Qianhong; Zhong, Hui; Sun, Yaxian; Yuan, Hui; Li, Shengnan; Shen, Zhongyuan; Wen, Ming (Frontiers in Ecology and Evolution, 2022)
Hemiculter leucisclus, as a widely distributed freshwater fish in China, provide an interesting model to explore the impact of drainage evolution and geologic history in Pleistocene on diversification patterns. We collected the mitochondrial cytochrome b (cytb) gene and the recombination activating gene 2 (RAG2) from 1070 individuals from 59 sampling locations. Phylogenetic and population genetic approaches were used to describe the phylogeographic pattern and to test how the geological and climatic factors on diversification. The results suggested that there existed four sublineages of the H. leucisclus across six river systems, among which two sublineages, showing strongly indigenous characteristics, are constrained to particular geographical regions in China. The molecular data and ancestral states demonstrated that the H. leucisclus possibly originated from the Pearl River basin during the later Pliocene. Phylogeographic pattern in H. leucisclus appears to have been driven by palaeoenvironmental perturbations rather than anthropogenic translocations. The geographically constrained sublineages A in middle and lower Pearl River basin and sublineage B in upper Yangtze River basin deserves special protection.